Find the numerical equivalent of 9^9⋅9^−6 . Your answer should be written without exponents.

1 answer

To find the numerical equivalent of \( 9^9 \cdot 9^{-6} \), we can use the properties of exponents. Specifically, we can combine the exponents since they have the same base:

\[ 9^9 \cdot 9^{-6} = 9^{9 + (-6)} = 9^{9 - 6} = 9^3 \]

Next, we need to calculate \( 9^3 \):

\[ 9^3 = 9 \cdot 9 \cdot 9 \]

Calculating step by step:

\[ 9 \cdot 9 = 81 \]

Now, multiplying by 9 again:

\[ 81 \cdot 9 = 729 \]

Thus, the numerical equivalent of \( 9^9 \cdot 9^{-6} \) is

\[ \boxed{729} \]